Vascular diagnosis and acute stroke: what, when and why not? - Szabo, Kristina; Lanczik, Oliver; Hennerici, Michael G. (Cerebrovascular diseases, 2005)
Even within the 3-hour time window, the less the delay to thrombolysis, the more likely it is to be effective. Delays caused by unnecessary examinations based on physicians' uncertainty about the relevance of vascular diagnostics must be overcome if acute therapy is to be administered efficiently. Only defined information concerning inclusion and exclusion criteria, a CT or preferably an MRI of the brain and limited additional data should be achieved prior to treatment and as quickly as possible, preferably within 1 h. All other information is to be gathered after the start of treatment, to assess the possible etiology of stroke, to classify the prognosis, and to recognize the possible need for early intervention such as in carotid stenosis. A primary diagnostic approach with MRI-guided treatment decision should be limited to cases with uncertain or 3- to 9-hour time window to improve selection of patients potentially at benefit from specific treatment and stroke unit/ICU care.
Gesehen am 10.05.2022